Population of Europe – From a Hungarian Perspective - Fűrész, Tünde; Pári, András; Rövid, Irén (Demographic Challenges in Central Europe: Legal and Family Policy Response, 2024)
Population-related questions, such as the population composition of a country, have been a concern for community leaders, professionals, and experts since the beginning of the formation of early societies. Over the last centuries, sociologists and demographers have conducted countless studies to identify the driving forces behind population trends, employing, for example, theories of demographic transitions and economics. At the regional level, the demographic situation is both specific and general, although there are marked differences not only between continents but also between countries within a continent. This is also the case in Europe. In general, we can see a strong and specific migration trend, with declining birth rates and total fertility rates. However, in some European countries, such as Hungary, the demographic picture over the last decade has differed from the overall population trends on the continent: fertility has risen, marriage rates are experiencing a renaissance, and migration has not been the solution to population issues. According to various United Nations estimates, Europe’s population is expected to decline in the coming decades. The consequences of this are somewhat noticeable today, and in those countries where they are felt, various policies are already being put in place to tackle – or try to ‘cure’ – this specific demographic ‘disease’. Since 2010, Hungary has been pursuing a pro-natalist and pro-family ‘national medicine’ policy, which uses measures to promote the well-being of families. This policy focuses on the family as the most important community, marriage as the most stable form of relationship, and respect for tradition and life. By building on internal resources, sustainability can be ensured in the national population of a country while preserving its economic, cultural, environmental, and value traditions. Keywords: demography, population, fertility rate, family policy